ANALYSIS OF REGRESSIVE MODELS OF HEART RATE VARIABILITY INDICATORS DEPENDING OF BODY ORGANIZATION, AGE AND HAND STRENGTH OF HEALTHY MALE AND FEMALE INDIVIDUALS OF EUCINETIC HEMODYNAMICS TYPE - Serheta, I.V.; Kovalchuk, V.V.; Dmytrenko, S.V.; Datsenko, G.V.; Ocheretna, O.L. (World of Medicine and Biology, 2017)
Using the regression analysis technique, we have built the individual models of heart rate variability indicators (HRV) based on the individual features of constitutional parameters of the body, age and hand strength with determination coefficients R2 less than 0.5 in practically healthy Podillia young men and women of eucinetic hemodynamics type. It was found that R2 determination coefficients of young men in 17 completed models ranged from 0.136 to 0.478, while in young women, R2 determination coefficients of 17 completed models ranged from 0.095 to 0.342. The models of young men most commonly covered the width of distal epiphyses of long tubular bones of the limbs (30.9%, mostly upper limbs), body circumference dimensions (15.7%, mainly at account of limbs) and body diameters (12.6%, mostly sagittal and transverse mid-thoracic size of the chest and pelvic measurement (Distancia cristarum)); and models of young women - age (35.3%), body weight components (13.7%, mainly at account of body muscle mass by Matiegka), width of distal epiphyses of long tubular bones of the limbs (at account of the lower extremities) and the hand strength (at account of the right hand) (11.8% each).